Synthesis of a New Inotropic Steroid Derivative and its Relationship with log P, p, Rm, Vm, Pc, St - Lauro, Figueroa-Valverde; Francisco, Diaz-Cedillo; Maria, Lopez-Ramos; Elodia, Garcia-Cervera; Quijano-Ascencio, K.A.; Cordoba-Vazquez, J.C. (Asian Journal of Chemistry, 2010)
In this work, a new inotropic steroid derivative was synthesized. The route involved preparation of furosemide-pregnenolone derivative by the reaction of furosemide with pregnenolone-succinate- ethylenediamine conjugate using a carbodiimide as catalyst. The biological activity of furosemide-pregnenolone and pregnenolone-succinate-ethylenediamine was evaluated in isolated rat hearts using Langendonff model. To delineate the structural chemical requirements of furosemide-pregnenolone as inotropic agent, other parameters such as the physicochemical descriptors log P, p, Rm, Vm, Pc and St were calculated. The results showed that the furosemidepregnenolone derivative significantly increase the perfusion pressure (p = 0.006), coronary resistance (p = 0.005) and intracellular calcium (1.35 × 10-3 to 2.70 × 10-3 mM) in isolated heart. Additionally, other data indicate that values of log P, p, Rm, Vm, Pc and St are high in the furosemidepregnenolone in comparison with pregnenolone-succinate-ethylenediamine. These data suggest that functional groups involved in the structure of furosemide-pregnenolone are specific for their positive inotropic activity.